Evaluation of antibacterial activity and acute toxicity of pomegranate (punica granatum l.) seed ethanolic extracts in swiss webster mice - Riani Setiadhi; Irna Sufiawati; Dewi Zakiawati; Nanan Nur’aeny; Wahyu Hidayat; Dani R. Firman (DiscoverSys Inc., 2017)
Objective: To evaluate the safety of a pomegranate seeds ethanolic extract in Swiss Webster mice.Material and Methods: Pomegranate seed’s ethanolic extracts were evaluated for minimum inhibitory concentration against streptococcus sanguis ATCC 10556, using microdilution method through 96-wells microplate. In acute toxicity test, 12 females and 12 males Swiss Webster mice weighing 20–30 grams were divided into four groups, each consisting of 3 females and 3 males. Three groups were orally given of sample with concentrations 0.2% equivalent to 40 mg/kg, 0.4% equivalent to 80 mg/kg, and 0.8% equivalent to 160 mg/kg, while the control group was given distilled water. Observations were made at 30, 60, and 90 minutes, for 24 hours and 7 days.Results: The MIC against Streptococcus sanguis was on 2000 ppm concentration and until 24 hours observation no lethal effect occurred on the mice, but at the 7 days observation in the group of 0.8% per kilogram body weight, the lethal effect occurred at one mice.Conclusion: The ethanolic extract of pomegranate seeds has antibacterial effect and no acute systemic toxicity, which can be considered safe on the use as oral topical solution since the toxic dose is greater than 160 mg/kg of body weight.